Der zweite Bananenzyklus in der Zona Atlántica Costa Ricas - Von der traditionellen Plantagenwirtschaft zum Kontraktanbau und zur ökologischen Modernisierung - Nuhn, Helmut (ERDKUNDE, 2003)
This paper presents a review of the basic conditions and determining factors for the construction of a new agro-industrial production complex in the Atlantic zone of Costa Rica, as seen against the background of the traditional plantation system which broke down here in the first half of the 20th century. It sets out the new division of labour between international export companies and national contract planters in the second banana cycle, as well as the problem of area requirements and intensification of production with their consequences for the natural environment. In conclusion, the paper offers a discussion and assessment of political and organizational starting points for ecological modernization and for the sustainable organization of export-orientated cultivation.